Pembuatan Dan Implementasi Standar Operasional Prosedur Klaim Barang Di Led Turbo Mojokerto - Permatasari, Anita (-, 2025)
This study aims to analyze the role of Standard Operating Procedures (SOP) in the product claim process from customers to LED Turbo as an essential part of quality management systems and customer service. SOPs serve as written guidelines that ensure consistency and efficiency at every stage of the claim process, from complaint reception and verification to claim resolution. A well-structured SOP can minimize errors, improve service transparency, and strengthen customer trust in the company. The findings affirm that SOPs function not only as internal control tools but also as indicators of the company's commitment to customer satisfaction at LED Turbo.